Evaluasi Stimulasi Hydraulic Fracturing Dan Kondisi Formasi Pada Reservoir Sandstone Di Sumur AML-14 - Aulia Miranti Larasathi; Amiruddin; Firdaus; Sulardi; Hamriyani Ryka; Ipan Sampe; Iin Darmiyati (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2021)
The reservoir layer in the FAY field is sandstone which is categorized as having low permeability. An evaluation was carried out on the AML-14 well to determine the cause of failure of the hydraulic fracturing work carried out on the well and its handlers The evaluation carried out in the FAY field included validating IPR data before hydraulic fracturing, pressure obtained during the step rate test, fracture geometry obtained after hydraulic fracturing, average permeability value, and increase in IPR value using the vogel method. Based on the results of the evaluation carried out, it can be seen that the pressure obtained during the step rate test was around 2602 Psi and the fracture flow rate was 1.2 Bpm which caused a screen out. The obtained fracture conductivity is about 6200 md-ft. The average permeability value obtained is 79 mD. The results of the fracturing carried out were that production decreased from the previous 154,626 Bopd to 15,757 Bopd. These results indicate that the hydraulic fracturing operation on the AML-14 well can be declared a failure due to a screen out that has an impact on production results that are not as expected. Handling of the well can be done by installing gravel pack conditions as well as slug pumping of sand which can effectively reduce the problem of placing sand into the wellbore.